Aspect sensitivity of polar mesosphere summer echoes based on ESRAD MST radar measurements in Kiruna, Sweden in 1997–2010 - M. Smirnova; E. Belova; S. Kirkwood (Annales Geophysicae, 2012)
Aspect sensitivities of polar mesosphere summer echoes (PMSE) measured with the ESRAD 50 MHz radar in 1997–2010 are studied using the full correlation analysis technique. Half of PMSE detected each year are found to be highly aspect sensitive. Yearly median values of the aspect sensitivity parameter θ s , characterising the half-width of the scatterers' polar diagram, are 2.9–3.7° depending on the year. The other half of the PMSE have θ s values larger than 9–11° and cannot be evaluated using the ESRAD vertical beam only. PMSE aspect sensitivity reveals an altitude dependence, namely, the scatter becomes more isotropic with increasing height. This result is consistent with that reported in other studies. No dependence of PMSE aspect sensitivity on backscattered power for any year was identified. In the paper the limitations of the in-beam and off-vertical beam methods for estimation of PMSE aspect sensitivity are discussed. We conclude that both methods should be combined in order to get complete information about PMSE aspect sensitivity and to estimate correctly PMSE absolute strength.